The Economics of Real Superstars: The Market for Rock Concerts in the Material World - Krueger, Alan B. (Journal of Labor Economics, 2005)
Beginning in 1997, the price of concert tickets took off and ticket sales declined. From 1996 to 2003, for example, the average concert price increased by 82%, while the CPI increased by 17%. Explanations for price growth include (1) the possible crowding out of the secondary ticket market, (2) rising superstar effects, (3) Baumols and Bowen's disease, (4) increased concentraion of promoters, and (5) the erosion of complementarities between concerts and album sales because of file sharing and CD copying. The article tentatively concludes that the decline in complementarities is the main cause of the recent surge in concert prices.